TINGKAT HIERARKI KEBUTUHAN ABRAHAM MASLOW PADA TOKOH UTAMA DALAM SERIAL TELEVISI YANG BERJUDUL GADIS KRETEK YANG DISUTRADARAI OLEH KAMILA ANDINI DAN IFA ISFANSYAH - Tarigan, Dina Mariana Br.; Monika, Santy (LPPM Universitas PGRI Silampari Lubuklinggau, 2025)
This study aims to identify five levels of hierarchy of needs according to Abraham Maslow's theory in the main character in the television series entitled Gadis Kretek. The research method used is descriptive qualitative, namely a research method that aims to examine the object or subject of research in detail, such as presenting information such as events, symptoms, and incidents as they are. The data collection technique used is the technique of observing and recording, while the data analysis technique uses a technique consisting of data reduction, then presenting the data and then drawing conclusions. The results of this study are the discovery of five levels of hierarchy of needs according to Maslow's theory, namely physiological needs, security needs, social needs, esteem needs and self-actualization needs. The main character Jeng Yah in the television series entitled Gadis Kretek has achieved the highest need of Maslow's five needs, namely the need for self-actualization. This is because the main character, Jeng Yah, has achieved four levels of Maslow's hierarchy of needs, namely physiological needs, security needs, social needs, and esteem needs.